Citizenship in the Digital Age: Implications and Challenges - I Kadek Adi Permana; I Kadek Agus Suardika Yasa; I Kadek Ari Dwi Saputra; I Putu Raditya Sudwika (Journal of Digital Law and Policy, 2023)
The significance of digital citizenship necessitates consideration in the context of an ever-evolving digital age. Digital citizenship is crucial in the digital age. This essay explores the importance of ethical digital citizenship in technology use. This study examines the implications and challenges of positive digital citizenship. This essay emphasizes digital citizenship and responsible technology use. Individuals and society must consider privacy, security, and ethics when using technology responsibly. Irresponsible technology use can lead to data misuse, propagating misinformation, and online violence. Additionally, this paper emphasizes digital citizenship ethics. Digital citizenship ethics include fairness, respecting others' rights, and fostering technology goodness. We must consider the social, political, and cultural effects of our digital activity. In tackling rising difficulties, this article suggests numerous ways to promote responsible and ethical digital citizenship. These measures include responsible technology usage education, ethical digital policies, and empowerment of individuals and communities to practice digital citizenship. Responsible and ethical digital citizenship can promote a more inclusive, safe, and beneficial digital environment for individuals and society. In an age where technology dominates our lives, digital citizenship must be part of active involvement in digital society.